Characterising murine hippocampal iron homeostasis, in relation to markers of brain inflammation and metabolism, during ageing - Ellison, Gae; Duong, Lelinh; Hollings, Ashley; Howard, D.; Jackaman, Connie; Hackett, Mark (OXFORD UNIV PRESS, 2022)
Metal ions (Fe, Cu, and Zn) are essential to a healthy brain function, with the amount, localisation, and chemical form often tightly controlled. Evidence points towards loss of metal ion homeostasis within the ageing brain; in particular brain Fe accumulation appears to be a hallmark of ageing, which may place the brain at a greater risk of neurodegenerative disease. Unfortunately, the cause or consequence of altered brain metal ion homeostasis during ageing remains unknown, and there is a lack of data comparing brain metal ion homeostasis with other events of the ageing process (e.g. brain metabolism, brain inflammation). This study has utilised a multi-modal approach that incorporated: X-ray fluorescence microscopy for elemental mapping of metal ion homeostasis, Perl's Fe histochemistry, FTIR spectroscopic biochemical imaging of lactate and protein aggregates, and immuno-fluorescence analysis of markers of brain inflammation and Fe storage proteins (heavy-chain ferritin, light-chain ferritin, and mitochondrial ferritin). Interestingly, while age-related Fe accumulation was observed in corpus callosum white matter of murine (C56BL/6J) brain tissue (concomitant with elevated levels of markers of brain inflammation and altered metabolism), Fe content was not altered within the hippocampus (a decrease in total Zn within the mossy fibres was observed). Ultimately, the results of this study demonstrate an important association between elevated brain Fe and brain inflammation during natural ageing. This study also highlights that future research is required to image different chemical forms of Fe with respect to changes in brain metabolism and inflammation, as well as localising these changes to specific cell types.